К вопросу о реликтовых и проектных формах хорового искусства Крыма ХІХ – начала ХХІ веков - Чергeeв, А.А. (Культура народов Причерноморья, 2014)
В статье рассматриваются реликтовые и проектные формы хорового искусства Крыма
ХІХ – начала ХХІ веков: дореволюционная модель государственного образования и роль хоров в
дореволюционных учебных заведениях, крымские конфессиональные и этнические школы, крымские
частные музыкальные школы, хоровые фестивали меннонитов в Крыму, крымское хоровое общество
советского периода; вокально–хоровая деятельность национально–культурных обществ Крыма, типы и
концепции современных хоровых фестивалей, татарская хоровая культура. Определена роль
реликтовых и проектных форм в музыкальной культуре региона. У статті розглядаються реліктові та проектні форми хорового мистецтва Криму ХІХ –
початку ХХІ століть: дореволюційна модель державної освіти та роль хорів у дореволюційних
навчальних закладах, кримські конфесійні та етнічні школи, кримські приватні музичні школи, хорові
фестивалі менонітів в Криму, кримське хорове товариство радянського періоду; вокально–хорова
діяльність національно–культурних товариств Криму, типи та концепції сучасних хорових фестивалів,
татарська хорова культура. Визначено роль реліктових і проектних форм в музичній культурі регіону. This article discusses the design and relict forms of choral art of the Crimea in XIX – the beginning
of XXI century: pre–revolutionary model of public education and the role of the choir in the pre–revolutionary
institutions, religious and ethnic Crimean schools, private music schools, choral festivals Mennonites in the
Crimea, Crimean choral society of the Soviet period, vocal and choral activities of national cultural societies of
the Crimea, types and concepts of modern choral festivals, choral Tatar culture. The role of the relic and design
forms in the musical culture of the region is researched.
Choral art in the Crimea developed in parallel with the other regions of the empire.
The Crimea's ethnic diversity is an important internal mechanism of its current state and design forms. Ethnic
pluralism of rapidly developing national–cultural societies of the Crimea relates to design forms.
We identified the following forms of Crimean choral culture. They still remain in the memory of society and thus
enrich the present, resonating and saturating modern forms of life and choral music making stereotype musical
consciousness culture.
Ethnic pluralism of contemporary musical and cultural activities of national cultural societies of the Crimea,
types and concepts of modern choral festivals. Crimean Tatar choral culture has been presented as design forms
of choral music. They already exist and develop in the region, but, in our opinion, they have the potential for
further development.